Campur Kode Bahasa Mahasiswa Universitas Negeri Padang Studi Analisis Terhadap Pelestarian Bahasa - Boty Eryanti; Dila Afrianika; Enjelly Maysi Putri; Jauzaa Syariifah Azzaroh; Juwita Alia; Farel Olva Zulve (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the use of code-mixing in WhatsApp conversations among Padang State University students, both with fellow students and with lecturers, and its relationship to language preservation. This study used a descriptive qualitative method with data in the form of written utterances in WhatsApp conversations. Data collection was conducted through screenshots and copies of conversations (chats) containing elements of code-mixing. The results of this study indicate that the dominant code-mixing used is external code-mixing in the form of English, such as "time," "list," and "deadline," as well as internal code-mixing involving regional languages. The use of code-mixing is influenced by language habits, practicality, and the influence of digital technology. This phenomenon has the potential to impact the preservation of Indonesian and regional languages if not accompanied by good language awareness.